US-ASEAN Relations: Uncertainty and Opportunity - Han, David (2016)
The recent US-ASEAN summit held last month underscores US commitment to Southeast Asia. Although it is uncertain whether this commitment would endure beyond the Obama administration, it is likely to continue due to the economic opportunity and security importance of the Asia-Pacific.